Economical Impacts of MOdernization on the Tappers of Ahmad Tohari's Bekisar Merah - Suparman, Suparman (Buletin Al-Turas, 2008)
This literary research is primariw aimed at revealing the economical impacts of modemizabon on the tappers in Bekisar Merah. The study uses terdisciplinary approach, which involves economical historical, cultural, ecological, and mimetic approaches. The analysis shows that the forms of modernization in Bekisar Merah are the impacts of the coming of electrification in the village. Modernization does not only cause positive impacts but also negative ones, which are stronger. The negative impacts include monopoly, human andcultural conflict, poverty, disharmony, greediness, law breaking, materialistic life, adultery, divorce, less religiosity, drop outs and migration. The positive impacts indude independence, adaptation, rationality,and efficiency. The problems appear in the novel rellects the inner conflict of the author, Ahmad Tohari He questions the ideas of the coming of electricity set in Karangsoga villase. Modernization can only be enjoyedby the upper class of the society. It cannot meet the nenes sity of the common people. The tappers loose somebenefits because of the coming of electricity in their village. They cannot enjoy the electricity, moreover, it caused misery and poverty.